2010
DOI: 10.1257/pol.2.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Time is Money: Choosing between Charitable Activities

Abstract: This paper analyzes the impact of a preferential tax-price for monetary donations on the joint decision to donate time (volunteer) and money. The methodological approach takes into account that consumption of each charitable good affects consumption of the other. Using data from a national survey on household charitable giving, the results show that donations of time and money are substitutes. However, a decrease in the tax-price of monetary donations also has a positive effect on donations of time that acts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 25 publications
3
72
0
Order By: Relevance
“…15 Again, this estimate is comparable with the estimates from other sources of charitable giving data. 16 In the COPPS, there exists a fairly broad distribution of the frequency of attendance at religious services ranging from no attendance to few people reporting attendance every day. On average, people reported attending at a religious service 2.5 times a month.…”
Section: Charitable Subsidies and Religiositymentioning
confidence: 99%
See 2 more Smart Citations
“…15 Again, this estimate is comparable with the estimates from other sources of charitable giving data. 16 In the COPPS, there exists a fairly broad distribution of the frequency of attendance at religious services ranging from no attendance to few people reporting attendance every day. On average, people reported attending at a religious service 2.5 times a month.…”
Section: Charitable Subsidies and Religiositymentioning
confidence: 99%
“…15 The average tax subsidy is simply calculated as one minus the after-tax price of giving. 16 Gruber (2004) reports that the average tax subsidy to charitable giving, factoring in the odds of itemization by income is 9.4% in the CEX, and 10% in the GSS. I estimate that the average subsidy in the 2001 edition of the SGV is 11.2%.…”
Section: Charitable Subsidies and Religiositymentioning
confidence: 99%
See 1 more Smart Citation
“…These kinds of programs are also popular with adolescents because the events require more time engagement than direct monetary engagement on the part of the participant. Feldman demonstrated that donations of time and money are interchangeable, and adolescents are more likely to have excess time than money available for charity [14]. From a positive youth development perspective [15], adolescents' participation in these sporting events are likely major developmental assets in terms of their ability to promote positive developmental outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Third, charitable monetary donations could be introduced. Money and time donations may be either substitutes or complements, implying that tax relief on time donations could affect monetary donations as well (see Brown and Lankford (1992), Duncan (1999), Andreoni, Gale, Scholz and Straub (2004) and Feldman (2010)). Fourth, a more explicit household decision making model could be formulated, rather than treating male labor supply as exogenous.…”
Section: Resultsmentioning
confidence: 99%